Single nucleus transcriptomics of ventral midbrain identifies glial activation associated with chronic opioid use disorder - Julong Wei; Tova Y. Lambert; Aditi Valada; Nikhil Patel; Kellie Walker; Jayna Lenders; Carl J. Schmidt; Marina Iskhakova; Adnan Alazizi; Henriette Mair-Meijers; Deborah C. Mash; Francesca Luca; et al. (Nature Communications, 2023)
Abstract Dynamic interactions of neurons and glia in the ventral midbrain mediate reward and addiction behavior. We studied gene expression in 212,713 ventral midbrain single nuclei from 95 individuals with history of opioid misuse, and individuals without drug exposure. Chronic exposure to opioids was not associated with change in proportions of glial and neuronal subtypes, however glial transcriptomes were broadly altered, involving 9.5 − 6.2% of expressed genes within microglia, oligodendrocytes, and astrocytes. Genes associated with activation of the immune response including interferon, NFkB signaling, and cell motility pathways were upregulated, contrasting with down-regulated expression of synaptic signaling and plasticity genes in ventral midbrain non-dopaminergic neurons. Ventral midbrain transcriptomic reprogramming in the context of chronic opioid exposure included 325 genes that previous genome-wide studies had linked to risk of substance use traits in the broader population, thereby pointing to heritable risk architectures in the genomic organization of the brain’s reward circuitry.